1977
DOI: 10.1111/j.1550-7408.1977.tb00991.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphofructokinase of Leishmania donovani and Leishmania braziliensis and its Role in Glycolysis*

Abstract: It was shown in an investigation of the phosphofructokinases of Leishmania donovani and Leishmania braziliensis that both enzymes are similar to that of Crithidia fasciculata. Although the enzymes are allosteric with respect to their substrates and require AMP for activation, there is no influence by other heterotropic modifiers. The Mg2+-ATP chelate activates these enzymes in a first order process and they can be inhibited by free ATP. The inhibition is reversed by the activator, AMP, in a competitive manner.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0
1

Year Published

1977
1977
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
4
10
0
1
Order By: Relevance
“…3) [31] similar to the observation previously reported for the T. brucei enzyme [5]. The PFK activity in Leishmania species [32–34] and in T. borreli (J. Van Roy, F. Opperdoes, N. Chevalier & P. A. M. Michels, unpublished results) is also known to be ATP‐dependent.…”
Section: Analysis Of Kinetoplastid Pfk Genessupporting
confidence: 82%
See 1 more Smart Citation
“…3) [31] similar to the observation previously reported for the T. brucei enzyme [5]. The PFK activity in Leishmania species [32–34] and in T. borreli (J. Van Roy, F. Opperdoes, N. Chevalier & P. A. M. Michels, unpublished results) is also known to be ATP‐dependent.…”
Section: Analysis Of Kinetoplastid Pfk Genessupporting
confidence: 82%
“…No activity (less than 1%) was observed when PP i (at concentrations up to 5 m m ) was used as alternative phospho donor. As reported previously for PFK of T. brucei [7] and other Leishmania species [32], the activity of the enzyme depends hyperbolically on the concentration of ATP. The kinetic behaviour of the expressed PFK was determined as a function of fructose 6‐phosphate at fixed, saturated ATP concentration (1.0 m m ), and in the presence or absence of AMP and GDP (Fig.…”
Section: Kinetics Of Leishmania Pfksupporting
confidence: 61%
“…According to Berens and Marr (1977), PFK, which is the key regulatory enzyme in the glycolysis of many organisms, does not play an important role in Leishmania. PFK in Leishmania, and in all trypanosomatids studied, is very little aected by the typical eectors of this enzyme in most glycolytic systems (Cazzulo 1992).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a decrease in the rate of oxidation of ribose seen in most of the data in Table 111. The factors responsible for control of the carbon flow through the PPP and EMP remain to be determined, but control does not appear to reside at hexokinase, glucose-6-phosphate dehydrogenase (l), or phosphofructokinase (2).…”
Section: Discussionmentioning
confidence: 99%
“…Hart et al (1 1) found that not only glucose but also fatty acids stimulated the respiration of promastigotes but that amino acids did not appear to be used as energy substrates. Both Steiger & Meshnick (23) and Hart & Coombs (10) report, however, that glutamate is consumed at a rapid rate during growth while alanine is excreted, and there is evidence that in enriched growth media, amino acids are major substrates during the early and mid-log phases of growth (2,22). Hart et al (1 1) showed that the rate of oxygen uptake by L. mexicana promastigotes was about the same on a per mg protein basis as the amastigotes from which they were derived.…”
mentioning
confidence: 99%